2020
DOI: 10.21037/tcr-20-2324
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted laparoscopic partial nephrectomy is a safe and effective option for clinical T2 renal cell carcinoma: a case-series from single-institution

Abstract: Background: Robot-assisted laparoscopic partial nephrectomy (RAPN) is increasingly used in the treatment of complex renal tumors, but it is still not commonly performed for T2 renal tumors and the reports of RAPN for renal tumors ≥7 cm were limited. Here we report our single-institution outcomes to evaluate the safety and efficacy of RAPN in treating T2 renal tumors. Methods: This study was designed as a case-series study. We retrospectively reviewed our database and finally identified 16 patients undergoing R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The incidental detection of renal masses is increasing according to more frequent utilization of ultrasonography, computed tomography (CT) and other imaging techniques ( 10 ). Laparoscopic partial nephrectomy (LPN) is the current standard of treatment for renal carcinoma, especially in patients with tumors <4 cm ( 1 , 2 , 11 , 12 ), we perform laparoscopic radical nephrectomy when there is no possibility for preserving the kidney. Laparoscopic renal surgery can be performed either transperitoneally (TP) or retroperitoneally (RP).…”
Section: Discussionmentioning
confidence: 99%
“…The incidental detection of renal masses is increasing according to more frequent utilization of ultrasonography, computed tomography (CT) and other imaging techniques ( 10 ). Laparoscopic partial nephrectomy (LPN) is the current standard of treatment for renal carcinoma, especially in patients with tumors <4 cm ( 1 , 2 , 11 , 12 ), we perform laparoscopic radical nephrectomy when there is no possibility for preserving the kidney. Laparoscopic renal surgery can be performed either transperitoneally (TP) or retroperitoneally (RP).…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Long et al [ 8 ] reported that RAPN showed good preservation of renal function and acceptable perioperative and oncologic outcomes in treating large renal tumors (>7 cm), suggesting that RAPN is a safe and effective procedure (WIT of 20.0 min, no patients died, and no local recurrence during a mean follow-up of 31.0 months). In a multicenter analysis conducted by 19 robotic centers, Bertolo et al [ 9 ] reported that RAPN showed acceptable outcomes in the treatment of large renal masses above T2 and that it was safely performed (WIT of 25 min, positive surgical margins [PSMs] in 20 patients [8%], 10 deaths and 25 recurrences/metastases during a follow-up period of 12 months).…”
Section: Large and Complex Renal Tumor In Rapnmentioning
confidence: 99%
“…Technological advances have fueled a paradigm shift from open surgery to minimally invasive techniques for PN (2). Indeed, minimally invasive approaches, including laparoscopic PN and more recently, robot-assisted (RA) procedures, have been increasingly accepted as a reliable surgical option for patients with small renal tumors, largely due to the refinement of surgical techniques and instruments (3,4).Compared with open nephron-sparing surgery (NSS), robot-assisted partial nephrectomy (RAPN) has achieved good results with accurate resection of tumors, protection of renal function, and prevention and control of perioperative complications (5)(6)(7). These advantages have resulted in a surge of robotic surgeries in hospitals.…”
Section: Introductionmentioning
confidence: 99%